Applications of Renewable Energy Technologies and Embodied Energy Concepts in Housing Complex at Bangalore India: A Case Study - et. al., Dr. Mahendra Joshi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is a large number of building design options for energy efficient building design; however, a careful blend of these options is required. The present paper studies the development of an eco-friendly and energy efficient housing complex called T-ZED (Total Zero Energy Development) in Bangalore India. Energy conservation options using CFL and LED based lamps and luminaries instead of incandescent bulbs have been achieved. Use of renewable energy sources, zero energy building materials and solar passive architecture to minimize thermal loads in buildings have been shown. The project has been compared with a housing complex where conventional energy and building materials are used in terms of reduction in embodied energy, CO2 (Carbon dioxide) emissions and operational energy and thus the benefits of zero energy development have been identified.